POSITIVE TRENDS IN AWARENESS OF HARMFUL EFFETCS OF HIGH SALT INTAKE - 10 YEARS CROATIAN ACTION ON SALT AND HEALTH (CRASH). DATA FROM 2008 AND 2017 WORLD HYPERTENSION DAYS. (June 2018) - Domislovic, V.; Dapic, K.; Milicic, B.; Matasin, M.; Bukal, N.; Capak, K.; Drenjancevic, I.; Gulin, M.; Cavrak, V. Herceg; Jelakovic, A.; Josipovic, J.; Kos, J.; et al.
Abstract: Objective: The aim of this study was to evaluate changes in general population attitude and awareness on harmful effects of high salt consumption ten years after Croatian national action on salt and health (CRASH) was launched. Design and method: Data on salt awareness were collected in individuals (aged 18 years or older) participating in the 2008 and 2017 World Hypertension Day in Croatia. In 2017 blood pressure (BP) was measured at 26 sites in 5 cities in Croatia from 10 AM to 2 PM in hospital open points, central squares and pharmacies. BP was measured by physicians, trained nurses, pharmacist or medical students. Along with BP measurements, a short questionnaire on hypertension awareness, salt intake and smartphone use was completed at the time of the interview. This action was organized and supported by the Croatian Society of Hypertension. Results: A total of 2175 subjects, 873 (40.1%) men, 1211 (59.9%) women were examined. Awareness that increased salt intake is harmful and associated with high BP significantly increased from 2008 to 2017 (65.3% vs.95.8%);in 2017 women are more aware (91.8% vs.87.3%;p = 0.013). Comparing to 2008, in 2017, population is much more informed about harmful effects of exaggerated salt intake from physicians (48.9% vs.89.1%). In 2017 more subjects are aware that they are eating too salty than they were in 2008 (27% vs.36.1%), and more men than women thinks they are eating too salty (36.1% vs.29.8%, p = 0.02). Comparing data from 2008 and 2017 the same proportion of women believes that they would be able to reduce salt intake if suggested (86.5% vs.85.8%), but significantly more men in 2017 compared to 2008 declared that they could follow recommendations for reducing salt intake (62% vs.83.9%). Although significantly more subjects in 2017 than in 2008 are aware that bread and bakery products are the main sources of salt intake (9.5% vs.20.9%), the majority (52%) still believes that smoked meat, salami etc. is the main pathway of salt ingestion. Conclusions: Significant improvements in awareness of harmful effects of high salt consumption were noticed in Croatia.